Фрейми на позначення природи і людини у художньому дискурсі (на матеріалі роману Т. Гарді «Тесс із роду д’Ербервіллів») - Козак, Софія Веніамінівна; Kozak, Sofiia V. (Житомирський державний університет імені Івана Франка, 2011)
У статті докладно розглянуто поняття дискурсу; представлено розмежування термінів "фрейм" та "фреймова структура"; здійснено аналіз фреймових структур у літературно-художньому дискурсі, що становлять собою мовні кореляти фреймів "Природа" і "Людина"; описано особливості їх вербального наповнення та функціонування в англомовному прозовому та поетичному дискурсах. In the present article the notion of discourse is thoroughly examined; the differentiation of the terms "frame" and "frame structure" is fulfilled; the frame structures of the belles-lettres discourse that are the language correlates of the frames "Nature" and "Man" are analyzed; the peculiarities of their verbal filling as well as their functioning in the English prose and poetry discourses are described.
Frames that Denote Nature and Man in the Belles-Lettres Discourse (on the material of the Th. Hardy’s "Tess of the d’Urbervilles")
Keywords: frame; frame structure; terminal; terminal element; discourse